d-Poly(e-caprolactone) (530)/siloxane biohybrid films doped with protic ionic liquids - Fernandes, M. (2017)
Organic/inorganic biohybrids composed of poly(ε-caprolactone) (PCL(530)) (where 530 represents the average molecular weight of the chains in gmol−1 ) chains covalently bonded to a siloxane network via urethane linkages and incorporating protic ionic liquids (PILs) were investigated. The materials (H-PILX, where H represents the host hybrid matrix and X is the ratio, in %, of the mass of PIL per mass of organic precursor) were doped with two different concentrations of N-ethylimidazolium trifluoromethanesulfonate ([EIm][TfO]) and N-butylimidazolium trifluoromethanesulfonate ([BIm][TfO]). The samples were processed as essentially amorphous and transparent films, thermally stable up to at least 200 °C. The highest ionic conductivity value (4.3 × 10−5 S cm−1 ) was measured for H-[EIm][TfO]16.4 at 105 °C. This work emphasizes that Scanning Electron Microscopy (SEM)/Energy Dispersive X-ray Spectroscopy (EDS) measurements are mandatory for the morphological characterization of IL-based electrolytes. In the case of the most concentrated [BIm][TfO]-doped hybrid studied this technique enabled the detection of segregated silica-rich circular micro-sized regions formed as a result of the hydrophobic interactions established between the bulky butyl chains of the [BIm]+ cation and the PCL(530) chains of the host matrix.